ANALISIS KINERJA APARAT DESA KECAMATAN TOMINI KABUPATEN BOLAANG MONGONDOW SELATAN - LUMALI, HARFAN; Rizal; Husain, Parni (LP2M Universitas Bina Mandiri Gorontalo, 2023)
AbstraK This research was carried out with the aim of knowing the performance of village officials about work discipline, employee abilities, and services provided. The Report Method used is Qualitative Research using data collection techniques carried out using observation techniques, interviews and documents. The author shows that the Performance Analysis of Village Officials in Tomini District, South BoaangMongondowRegency, Village Officials are an Important Component in determining the service system to the community as a whole, which must receive careful attention.